The effects of dependent interviewing on responses to questions on income sources - Peter Lynn; Annette Jäckle; Stephen P. Jenkins; Emanuela Sala (Deutsches Institut für Wirtschaftsforschung (DIW), 2005)
Using an experimental design, we compare two alternative approaches to dependent interviewing (proactive and reactive) with traditional independent interviewing on a module of questions about sources of income. We believe this to be the first large-scale quantitative comparison of proactive and reactive dependent interviewing. The three approaches to questioning are compared in terms of their impact on under-reporting of income sources and related bivariate statistics. The study design also enables identification of the characteristics of respondents whose responses are sensitive to the mode of interviewing. We conclude that under-reporting can be significantly greater with independent interviewing than with either form of dependent interviewing, especially for income sources that are relatively common or relatively easy to forget. We find that dependent interviewing is particularly helpful as a recall aid for respondents below retirement age and registered disabled persons.
Keywords: 330